1H and 31P benchtop NMR of liquids and solids used in and/or produced during the manufacture of methamphetamine by the HI reduction of pseudoephedrine/ephedrine. (September 2017) - Bogun, Ben; Moore, Sarah
Highlights: Evaluation of benchtop NMR for drug and clandestine laboratory analysis. Ability to distinguish between structurally similar compounds. Can identify both phosphorous and organic compounds. Assist in interpretation of whether methamphetamine had been manufactured. Abstract: In this study, the use of benchtop NMR spectroscopy in the analysis of solids and liquids used and/or produced during the HI reduction of pseudoephedrine was evaluated. The study focused on identifying organic precursors and phosphorus containing compounds used in and/or produced during the manufacturing process. Samples taken from clandestine laboratories, where this synthesis process was suspected of occurring, were also analysed and evaluated. Benchtop NMR was able to distinguish between ephedrine, pseudoephedrine and methamphetamine as the free base and hydrochloride salt. This technique was also effective at identifying and distinguishing between phosphorus containing compounds used and/or produced during the manufacture of methamphetamine. Benchtop NMR was also determined to be effective at analysing samples from suspected clandestine laboratories.